Successful attitude skills (Rugeley : Focus Multimedia Limited, 2005)
A multimedia course designed to help you assess your attitude skills and resolve any problems, providing a guide to a more positive and successful attitude.
Ελάχιστες απαιτήσεις συστήματος: IBM compatible PC; Pentium 133 processor or equivalent; 32 MB RAM; Windows 98 or later; 80 MB of free hard disk space.
Keywords: CD-ROMs.; Attitude (Psychology) -- CD-ROMs.; Success in business -- CD-ROMs.